Effect of graded levels of Moringa oleifera leaf meal on growth, haematology and serum biochemistry of African catfish Clarias Gariepinus juveniles - Omitoyin, Siyanbola Adewumi; Orisasona, Olugbenga; Ajani, Kolawole Emmanul; Omitoyin, Bamidele Oluwarotimi (Aceh Journal of Animal Science, 2023)
The effects of the leaf meal ofMoringa oleifera(MLM) as a source of protein in the diet ofClarias gariepinususing growth, haematology and serum biochemistry as indicators were investigated. Four experimental diets MLM1, MLM2, MLM3 and MLM4 were formulated, withM. oleiferaleaf meal replacing fish meal at 0%, 10%, 20% and 30% levels of inclusion.The four diets were allotted to triplicate groups of one hundred and eighty (180)C. gariepinus(12.50.03g mean weight) randomly distributed into 12 plastic aquaria for 84 days at 3% body weight daily. Growth variables including Mean weight gain (MWG), Specific growth rates (SGR), Feed conversion ratio (FCR) and Survival were determined using standard procedures. Samples of blood were collected from randomly selected fish samples before and after the feeding trial for haematological and serum biochemical analysis. Results show that MLM has fat, crude protein, crude fibre and ash contents of 5.34%, 26.62%, 18.97% and 12.01% respectively. Mean weight gain was significantly higher in MLM1 and MLM2 groups (16.750.35g and 15.490.22g respectively), with these groups having superior FCR values. Survival rate was 95% across treatment. PCV and blood platelets were significantly higher (P0.05) in fish fed MLM diets.Creatinine and total protein showed significantly higher values in the control group with values ranging from 0.40 (MLM3) to 0.67 (MLM1) and 3.16 (MLM3) to 4.70 (MLM1) and respectively.The results indicate that the leaf meal ofMoringa oleiferacan only replace up to 10% fish meal inClarias gariepinusdiets when growth and haematological parameters are considered.